(untitled) (Papeles, 2021)
This paper analyzes the local implementation of the Uruguayan Law of Land Use and Sustainable Development in an intermediate city with a slow population increase but with significant changes in the use and activities of its peripheral land. In this sense, the inquiry stops at the treatment that, from the diagnosis and proposal, the planning instrument raises of the rural-urban border areas. In this way, it is possible to appreciate peri-urbanization phenomena outside the metropolitan territories, and the role of long-term trends in land occupation, placing the framework of land use planning to consolidate a territorial model that shows more inertia than innovation.